Gutes Klima für die Zukunft. Dekarbonisierung als wichtiger Schlüssel zum nachhaltigen Bauen mit Beton 18. Symposium Baustoffe und Bauwerkserhaltung, Karlsruher Institut für Technologie (KIT), 10. März 2022 - Nolting, Ulrich; Dehn, Frank; Mercedes Kind, Vanessa (KIT Scientific Publishing, 2022)
How can we manage the growing demand for housing and the increasing desire for sustainability and climate protection at the same time? And how can the various stakeholders in the concrete construction industry contribute? The present conference proceedings provide an overview of the opportunities and challenges of sustainable concrete construction and show with exciting examples which paths industry, regulators and the public sector are taking to achieve climate-neutral construction.